A multi-roller static model of the planetary roller screw mechanism considering load sharing. (September 2022) - Fu, Xiaojun; Li, Xin; Ma, Shangjun; Gerada, David; Liu, Geng; Gerada, Christopher
Abstract: A multi-roller static model is proposed to calculate load sharing and load distribution in a planetary roller screw mechanism (PRSM) with axial loads and errors. Taking into the actual positions of rollers, the PRSM is discretized into a multi-roller spring system. The proposed model is validated by comparing the results from a finite element model. The load sharing, load distribution and elastic deformation behaviors of a PRSM under different part position errors and thread index errors are analyzed. The results show that load sharing is sensitive to the position errors of the screw and nut while being fairly insensitive to those of rollers. Part position errors and thread index errors have a great influence on the stiffness of the PRSM. Highlights: The PRSM is discretized into a multi-roller spring system. The load sharing behaviors of the PRSM caused by axial loads and errors are analyzed. Load sharing has a considerable influence on the contact forces acting on threads. Load sharing improves as the axis of the nut is coincident with that of the screw.